A Qualitative Analysis of Hospital Leaders’ Opinions About Publicly Reported Measures of Health Care Quality - Goff, Sarah L. (Jt Comm J Qual Patient Saf, 2015)
BACKGROUND: Hospital leaders play an important role in the success of quality improvement (QI) initiatives, yet little is known about how leaders engaged in QI currently view quality performance measures. In a follow-up to a quantitative study conducted in 2012, a study employing qualitative content analysis was conducted to (1) describe leaders’ opinions about the quality measures reported on the Centers for Medicare & Medicaid Services (CMS) Hospital Compare website, (2) to generate hypotheses about barriers/facilitators to improving hospitals’ performance, and (3) to elicit recommendations about how to improve publicly reported quality measures. METHODS: The opinions of leaders from a stratified sample of 630 hospitals across the United States regarding quality measures were assessed with an open-ended prompt that was part of a 21-item questionnaire about quality measures publicly reported by CMS. Their responses were qualitatively analyzed in an iterative process, resulting in the identification of the presence and frequency of major themes and subthemes. RESULTS: Participants from 131 (21%) of the 630 hospitals surveyed replied to the open-ended prompt; 15% were from hospitals with higher-than-average performance scores, and 52% were from hospitals with lower-than-average scores. Major themes included (1) concerns regarding quality measurement (measure validity, importance, and fairness) and/ or public reporting; 76%); (2) positive views of quality measurement (stimulate improvement, focus efforts; 13%); and (3) recommendations for improving quality measurement. CONCLUSIONS: Among hospital leaders responding to an open-ended survey prompt, some supported the concept of measuring quality, but the majority criticized the validity and utility of current quality measures. Although quality measures are frequently being reevaluated and new measures developed, the ability of such measures to stimulate improvement may be limited without greater buy-in from hospital leaders.